Analisa Pengaruh Leadership Style Terhadap Organization Performance Melalui Learning Organization dan Employee Satisfaction (Studi Kasus pada Akuntan Publik di Kantor Akuntan Publik di Surabaya) - Stephanie Yunita Nathania (Business Accounting Review, 2015)
This study aimsed to know the direct and significant influence of leadership style to organizational performance through learning organization and employee’s satisfaction in the public accounting firm in Surabaya. This was a of quantitative research by obtaining primary data. The data obtained by distributing questionnaires to 150 auditors in the public accounting firm’s in Surabaya. The data obtained were processed by using data PLS.The results indicated the existency of a significant relationship between the leadership style to the learning organization, learning organization to organization performance, leadership style on employee’s satisfaction, employee’s satisfaction to organization performance, and leadership style to organizational performance. Learning organization and employee satisaction were intermediary variable of the variables of leadership style and employee’s satisfaction, because they were not able to strengthen the influence of leadership style on performance organization directly.